2013
DOI: 10.21273/hortsci.48.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mechanical String Thinning Treatments on Vegetative and Reproductive Tissues, Fruit Set, Yield, and Fruit Quality of ‘Gala’ Apple

Abstract: The objectives of this experiment were to test the efficacy of a mechanical string thinner (Darwin PT-250; Fruit-Tec, Deggenhauserertal, Germany) on apple and to identify an optimal range of thinning severity as influenced by spindle rotation speed. Trials were conducted in 2010 and 2011 at the Pennsylvania State University Fruit Research and Extension Center in Biglerville, PA, on five-year-old ‘Buckeye Gala’/M.9 apple trees that were trained to tall spindle. A preliminary trail on five-year-old ‘Crip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 11 publications
6
20
0
Order By: Relevance
“…Although spur and limb damage were generally low due to machine harvest, they were almost twice as great as compared with hand harvest. Although this amount of tree damage may not directly impact yield, open wounds may be sites for infection of important diseases such as fire blight (Erwina amylovora), leading to significant effects on long term orchard health and yield (Kon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although spur and limb damage were generally low due to machine harvest, they were almost twice as great as compared with hand harvest. Although this amount of tree damage may not directly impact yield, open wounds may be sites for infection of important diseases such as fire blight (Erwina amylovora), leading to significant effects on long term orchard health and yield (Kon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Mcclure and Cline (2015) with a Darwin ® machine at 3.2 km•h -1 and 180-240 rpm did not observe a significant yield reduction on 'Royal Gala ® '. Both Kon et al (2013) with a Darwin ® , and Damerow et al (2007) with a Baum ® machine, reported higher blossom removal as rotational speed increased. On the other hand, a study conducted by Sinatsch et al (2010) on 'Pinova cov ', did not reveal significant differences when maintaining a tractor speed at 3.2 km•h -1 , and rotational speeds from 200 to 220 rpm.…”
Section: Discussionmentioning
confidence: 93%
“…Seehuber et al (2014b) suggested E2 to F2 as the ideal timing window for mechanical thinning, whereas a wider window was suggested by Veal et al (2011) (E2 to G). Hence, reference studies have been performed at different stages like F1 (Basak et al, 2016;Mcclure and Cline, 2015), pink bud (E2) to full bloom (F2) (Miranda Sazo et al, 2016;Solomakhin et al, 2012;Veal et al, 2011), at full bloom (F2) (Hehnen et al, 2012;Kirstein, 2015;Kon et al, 2013;Solomakhin and Blanke, 2010), or even at 30% of petal fall (Kirstein, 2015). The fact that mechanical thinning is less dependent on phenological stage than timing of chemical thinners will allow more time to manage different spring situations, like spring frost forecasts, in order to delay the treatment for safety reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Dashed line marks the mean value. J o u r n a l o f H o r t i c u l t u r a l S c i e n c e to our knowledge, applied in practice ranging from 2.5 km h -1 to 12.0 km h -1 (Kon et al, 2013). At rotational frequency of 380 rpm, this difference in tractor speed caused a maximum spread of 0.19 J, regarding the angle of the string at 135° to the driving direction.…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative, devices for mechaniyears with more reliable effects (Schröder, 1996 , 1998;Damerow et al, 2007). The principle is based on a driven by a mechanical or hydraulic system, which allows the length of strings, the rotational frequency and the speed of er removal (Zoth, 2011;Kon et al, 2013;Penzel et al, 2020) by the enhanced kinetic energy (E kin ), which is transferred by the strings into the canopy. The speed of the tractor inand Blanke (2010) regards most of these factors and also incompared to the effect of the thinning intensity.…”
Section: Introductionmentioning
confidence: 99%